Education on Handling Dysmenorrhea in Adolescents at SMA it Insan Cendekia Doyo Baruon Elderly Gymnastics to Improve Sleep Quality in The Elderly - Susi Lestari; Endah Purwanti Handayani; Eftyaningrum Dwi Astutik; Harlinda Widia Putri; Hasnia; Tiyan Febriyani Lestari; Yustika Rahmawati Pratami; Wiwit Vitania; Keryn Amanda Palino; Yurida Awairaro; Jenny F Wally; Ancelince Agapa; Nosti Wetapo; Nadia Dude (STIKes Patria Husada Blitar, 2023)
Dysmenorrhea is a medical term that occurs during menstruation and causes pain caused by uterine contractions. Dysmenorrhea is not a disease but a problem that periodically makes a woman feel uncomfortable during her menstrual period. The purpose of this community service is to increase the understanding of adolescents in SMA IT Insan Cendekia Kabupaten Jayapura about the handling of dysmenorrhea. The implementation of this community service activities was at namely SMA IT Insan Cendekia Kabupaten Jayapura povinsi Papua, Jl. Yowanibi-Polres, Doyo Baru, Kecamatan Waibu. The partners in this activity were young women who were in the in SMA IT Insan Cendekia Kabupaten Jayapura area as many as 20 teenagers. The activity began with the opening, presentation of material, and post test orally exam. The final result of the counseling activity was as many as 90% of adolescents who gave positive responses and experienced an increase in understanding about dysmenorrhea and an increase in knowledge from an average score of 1 to 8.88 which was seen from the enthusiasm of adolescents when listening to the material and answering the questions asked and great appeal to apply what has been given.